Comparison of the lower extremities' explosive muscular strength via jumping tests in different performance level and age groups of women volleyball players - Jakubsová, Z.; Vaverka, F.; Jandacka, D. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2011)
BACKGROUND: Sport performance in volleyball is significantly influenced by the quality of the player´s jumping abilities, above all on the height of the jump. Results in jumping tests indirectly indicate information about explosive muscle strength. Information about the quality of the results of jumping tests is the starting point for the monitoring of the athlete`s conditioning. OBJECTIVE: This work´s purpose consists in finding out whether there exist some differences between women volleyball players according to their age and their sport performance level and whether women volleyball players differ from women university students. A secondary aim of the study is to assess the suitability of using three jumping tests in volleyball. METHODS: For the set of women volleyball players (n = 273) divided into five different age and sport performance categories and for the set of university female students (n = 33), three jump tests were applied:the spike jump test SPJ, the counter movement jump test CMJ and the standing broad jump test SBJ. Statistical analysis was done using the Czech STATISTICA system, version 6 (Kolmogorov-Smirnov test, Spearman coefficient correlation, paired t-test and ANOVA for independent samples). RESULTS: Relatively small and mostly statistically insignificant differences have been found between women volleyball players of various age and sport performance groups. All groups of volleyball players significantly exceeded the university students set in the level of their explosive muscle strength. Our research showed a lower level of jump performance, especially in what concerns the highest sport performance of women players. The initial hypotheses about the usefulness of applying three jumping tests in volleyball were confirmed. CONCLUSIONS: The differences in the results of jumping tests for different age and sport performance groups of women volleyball players are small. The relatively lower level of the jumping abilities of the highest sport performance players was discovered. Experience with applying three jumping tests have shown their convenience to be utilizable in volleyball. Each test has its own specificity to provide information about the quality of jumping abilities with regards to the sport performance level and to the age of the tested female players.